Polyolefin elastomer particles, and methods of making and using the same
Patent Information
- Application Number
- CN202511191330.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-25
- Publication Date
- 2026-09-25
- Estimated Expiration
- 2045-08-25
AI Technical Summary
[0004]因此,本申请要解决的技术问题在于克服现有技术中的POE封装胶膜存在的助剂易析出、剥离强度衰减以及抗PID性能有待进一步提升等缺陷,从而提供一种聚烯烃弹性体粒子及其制备方法和应用
[0031]本申请提供的聚烯烃弹性体粒子的制备方法,包括如下步骤:S1,将聚烯烃弹性体、接枝单体、引发剂、紫外光稳定剂、抗氧剂进行反应,得到混合物料;S2,将混合物料挤出,在含有催化剂的水中进行切粒,得到反应粒子;S3,将所述反应粒子进行表面粗糙化处理,得到聚烯烃弹性体粒子。本申请中,通过在制备过程中引入功能单体以及在水下切粒中引入催化剂,并配合对反应粒子表面进行粗糙化处理,能够提高聚烯烃弹性体(POE)的极性,促进POE树脂对助剂的吸收速率,防止助剂析出,提升胶膜与基体的粘接力,同时保持POE优异的耐热、耐候性能和抗PID性能。
Smart Images

Figure CN120944021B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of polyolefin materials technology, specifically relating to a polyolefin elastomer particle, its preparation method, and its application. Background Technology
[0002] In recent years, polyolefin elastomers (POE) have been widely used in photovoltaic encapsulation films due to their excellent water vapor barrier properties, weather resistance, and high strength. However, as a non-polar material, POE has poor absorption of small-molecule functional additives added during film processing. After prolonged storage, liquid additives may migrate to the film surface, causing slippage between the film and the solar cell and glass, affecting the yield of module fabrication. Furthermore, additives in POE films are prone to precipitation, affecting the crosslinking rate during lamination with the solar cell and the degree of crosslinking after lamination. This leads to decreased peel strength and delamination from the solar cell during later aging processes, making the cells susceptible to potential-induced degradation (PID), especially pronounced in double-glass modules. Ultimately, this results in reduced power generation efficiency and a shorter lifespan for the cells.
[0003] To address these issues, researchers have explored various methods to improve the performance of POE. One common method is co-extruding ethylene-vinyl acetate copolymer (EVA) and polyolefin elastomer (POE) into EPE films. However, this method still suffers from inconsistencies in modulus and tensile stress between EVA and POE, and the tendency for additives in the POE layer to migrate to the EVA layer, leading to delamination between EVA and POE and lamination bubble formation. Another approach involves introducing polar monomers, such as POE-grafted polymers, to increase the polarity of POE. This method can improve the compatibility of POE with additives and increase the absorption rate of additives by the POE resin. However, currently used POE grafting methods, such as reactive extrusion processes, suffer from drawbacks such as low grafting rates, uneven distribution of grafted side chains, and large amounts of residual initiators and grafted monomers. POE with low grafting rates cannot provide sufficient polar functional groups, thus failing to effectively reduce additive migration between POE and EVA. Uneven grafting distribution, residual initiators, and grafted monomers can cause uneven cross-linking during subsequent lamination of the encapsulated film, leading to problems such as bubbles and affecting the overall performance of the battery. Existing technologies also involve preparing particles grafted with anti-PID additives before formulating the encapsulated film. However, the migration of additives in the encapsulated film is mainly due to silane coupling agents, and the anti-PID additives themselves are monomers with relatively large molecular weights. Grafting them first results in significant energy consumption, and the effect is not substantial. Summary of the Invention
[0004] Therefore, the technical problem to be solved by this application is to overcome the defects of existing POE encapsulation films, such as easy precipitation of additives, attenuation of peel strength, and the need for further improvement of anti-PID performance, so as to provide a polyolefin elastomer particle, its preparation method and application.
[0005] Therefore, this application provides the following technical solution:
[0006] According to one aspect of this application, a method for preparing polyolefin elastomer particles is provided, comprising the following steps:
[0007] S1, reacting polyolefin elastomer, graft monomer, initiator, UV stabilizer and antioxidant to obtain a mixture;
[0008] S2, the mixture is extruded and pelletized in water containing a catalyst to obtain reaction particles;
[0009] S3, the surface of the reactant particles is roughened to obtain polyolefin elastomer particles.
[0010] This application targets the grafting of easily migrating silane coupling agents. A surface roughening process is used to increase the surface roughness of the particles, which reduces additive migration and improves particle absorption of additives. This ensures the crosslinking rate during film-to-cell lamination and the degree of crosslinking after lamination, thus maintaining a reduced potential-induced degradation (PID) level. Specifically, this application introduces functional monomers during the preparation process and a catalyst during underwater pelletizing, along with surface roughening treatment of the reactant particles. This increases the polarity of the polyolefin elastomer (POE), promotes the absorption rate of additives by the POE resin, prevents additive precipitation, and enhances the adhesion between the film and the matrix, while maintaining the excellent heat resistance, weather resistance, and PID resistance of POE. Specifically, the initiator decomposes into initiator free radicals under heating conditions, which initiate the grafting of monomers to generate monomer free radicals. The initiator free radicals remove active hydrogen from POE, and the monomer free radicals undergo a grafting reaction with POE, increasing the polarity of POE. Granulation is carried out in water containing the catalyst, and the catalyst is uniformly dispersed on the particle surface. After the catalyst is uniformly loaded, the additives in the film will react uniformly with the catalyst to form oligomers, avoiding the migration and precipitation of additives. The roughening treatment can increase the surface roughness of the particles. With a large particle surface area, the additives in the film can be fully adsorbed into the particle interior, making subsequent migration more difficult (melt solid phase migration process). In addition, the preparation method of polyolefin elastomer particles provided in this application is simple and easy to promote and apply.
[0011] In some optional embodiments, in S2, the ratio of catalyst to water in the catalyst-containing water is 0.05-3 mg / kg, and the water temperature is 5-10°C. As an example, the ratio of catalyst to water in the catalyst-containing water is 0.05 mg / kg, 0.1 mg / kg, 0.5 mg / kg, 0.8 mg / kg, 1 mg / kg, 1.5 mg / kg, 2 mg / kg, 2.5 mg / kg, 3 mg / kg, or within any range of the above values; the water temperature can be 5°C, 6°C, 7°C, 8°C, 9°C, 10°C, or within any range of the above values.
[0012] In some alternative embodiments, the catalyst includes at least one of a tin-containing catalyst or a bismuth-containing catalyst;
[0013] Optionally, the catalyst includes at least one of dioctyltin, triphenyltin, dibutyltin dilaurate, bis(monoctyl maleate) di-n-butyltin, di-n-octyltin maleate, and bismuth neodecanoate.
[0014] In some alternative embodiments, the grafting monomer comprises a silane coupling agent;
[0015] Optionally, the grafting monomer includes at least one of sulfur-containing silane coupling agents, aminosilane coupling agents, epoxysilane coupling agents, vinylsilane coupling agents, and methacryloxysilanes.
[0016] Further optionally, the grafting monomer includes at least one of 3-(methacryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 1,2-bis(trimethoxysilyl)ethane, 1,2-bis(triethoxysilyl)ethane, and vinyltri(2-methoxyethoxy)silane.
[0017] In some alternative embodiments, in S3, a vibrating screen is used to roughen the surface of the reaction particles;
[0018] Optionally, the roughness Ra of the coarse vibrating screen is ≥1.5μm, and optionally the roughness is 1.5-10μm; the length of the vibrating screen is 1-3m; and the power of the vibrating screen is 10-30kW.
[0019] In some alternative embodiments, in S1, the reaction temperature is 180-220°C, and the reaction time (i.e., residence time) is 1-8 min, optionally 1-5 min. As an example, the reaction time can be 1 min, 2 min, 4 min, 5 min, 6 min, 8 min, or within any range of the above values.
[0020] In this application, for ease of operation, the reaction can be carried out directly in a twin-screw extruder.
[0021] In some alternative embodiments, the mass fractions of each component are as follows: 100 parts polyolefin elastomer, 0.5-10 parts graft monomer, 0.05-0.5 parts initiator, 0.05-0.3 parts UV stabilizer, and 0.1-0.6 parts antioxidant.
[0022] As an example, for 100 parts of polyolefin elastomer, the corresponding amount of grafted monomer can be 0.5 parts, 1 part, 3 parts, 5 parts, 7 parts, 9 parts, 10 parts, or within any range of the above values; the amount of initiator can be 0.05 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, or within any range of the above values; the amount of UV stabilizer can be 0.05 parts, 0.1 parts, 0.15 parts, 0.2 parts, 0.25 parts, 0.3 parts, or within any range of the above values; the amount of antioxidant can be 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, or within any range of the above values.
[0023] In some alternative embodiments, the polyolefin elastomer includes at least one of ethylene-propylene copolymer, ethylene-butene copolymer, ethylene-hexene copolymer, ethylene-octene, styrene-butadiene-styrene block copolymer, and ethylene-propylene-α-olefin copolymer;
[0024] And / or, the initiator includes at least one of organic peroxide initiators, inorganic peroxide initiators, azo initiators, and redox initiators, and optionally includes at least one of 2,5-dimethyl-2,5-bis(tert-butylperoxide)hexane, dicumyl peroxide, di-tert-butylperoxide, tert-butyl peroxide-2-ethylhexyl carbonate, tert-butyl peroxide-2-ethylhexyl carbonate, and tert-amyl peroxide-2-ethylhexyl carbonate.
[0025] And / or, the UV stabilizer comprises at least one of tris(1,2,2,6,6-pentamethyl-4-piperidinyl) phosphite, hexadecyl 3,5-di-tert-butyl-4-hydroxybenzoate, bis(2,2,6,6-tetramethylpiperidinyl) sebacate, and bis(1-octoxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate;
[0026] And / or, the antioxidant comprises one of 2,6-di-tert-butyl-p-cresol, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexamethylenediamine, 4,4'-thiobis(3-methyl-6-tert-butylphenol), and tris(2,4-di-tert-butylphenyl)phosphite.
[0027] In some optional embodiments, in S2, extrusion is performed using a twin-screw extruder with an aspect ratio (L / D) ≥ 55, optionally 56 ≤ L / D ≤ 65. As an example, the aspect ratio (L / D) of the twin-screw extruder can be 55, 56, 58, 60, 62, 64, 65, 66, 68, or within any range of these values. In this application, a longer aspect ratio ensures sufficient reaction time and improves the monomer grafting rate. Furthermore, a twin-screw extruder with a large aspect ratio can be designed with more functional sections (such as conveying, melting, mixing, and reaction sections), and different helical structures (such as kneading blocks and reverse threads) can enhance shearing and dispersion, ensuring uniform mixing of the POE melt, monomer, and initiator, providing a uniform microenvironment for the grafting reaction. POE grafting reactions are highly sensitive to temperature and shear strength. Extruders with a large length-to-diameter ratio can divide the screw into multiple independent temperature control zones (e.g., 5-10 zones), gradually adjusting the temperature from the feed inlet to the die head to precisely control the initiator decomposition rate and grafting reaction progress. Simultaneously, by designing the screw edges of different zones (e.g., low-shear conveying and melting in the front, high-shear mixing and reaction in the middle, and low-shear stabilization in the rear), the needs of each reaction stage are matched, avoiding localized overheating or shear imbalance. As an elastomer, POE exhibits high elastic recovery after melting. If the screw length is insufficient (small length-to-diameter ratio), the material is prone to forming a "dead zone" (retention) within the barrel, leading to localized overheating and degradation. A screw with a large length-to-diameter ratio, through continuous and stable conveying and shearing, can reduce material retention. Furthermore, a reasonable screw edge gap design ensures uniform material propagation along the screw axis, preventing cross-linking or degradation caused by retention.
[0028] According to another aspect of this application, a polyolefin elastomer particle is provided, which is prepared by the above-described preparation method.
[0029] According to another aspect of this application, an application of the above-mentioned polyolefin elastomer particles in an encapsulant film is provided; optionally, an application in a photovoltaic encapsulant film.
[0030] The technical solution of this application has the following advantages:
[0031] The method for preparing polyolefin elastomer particles provided in this application includes the following steps: S1, reacting polyolefin elastomer, graft monomer, initiator, UV stabilizer, and antioxidant to obtain a mixture; S2, extruding the mixture and pelletizing it in water containing a catalyst to obtain reaction particles; S3, subjecting the reaction particles to surface roughening treatment to obtain polyolefin elastomer particles. In this application, by introducing functional monomers during the preparation process and introducing a catalyst during underwater pelletizing, and by coordinating with surface roughening treatment of the reaction particles, the polarity of polyolefin elastomer (POE) can be improved, the absorption rate of additives by POE resin can be promoted, additive precipitation can be prevented, and the adhesion between the film and the matrix can be enhanced, while maintaining the excellent heat resistance, weather resistance, and anti-PID properties of POE.
[0032] The electrical equipment provided in this application has the same advantages as the aforementioned polyolefin elastic particles because it uses the polyolefin elastic particles provided in this application, which will not be repeated here.
[0033] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description
[0034] To more clearly illustrate the technical solutions in the specific embodiments of this application or the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0035] Figure 1 This is a 500x magnified SEM image of the polyolefin elastomer particles provided in Example 1 of this application;
[0036] Figure 2 This is a 500x magnified SEM image of the polyolefin elastomer particles provided in Comparative Example 2 of this application. Detailed Implementation
[0037] The following embodiments are provided to better understand this application and are not limited to the preferred embodiments described herein. They do not constitute a limitation on the content and scope of protection of this application. Any product that is the same as or similar to this application, derived by anyone under the guidance of this application or by combining features of this application with other prior art, falls within the scope of protection of this application.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having” and any variations thereof in the text of this application are intended to cover non-exclusive inclusion.
[0039] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0040] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of the specific range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers from a to b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed herein, and "0-5" is merely a shortened representation of these numerical combinations. Furthermore, when a parameter is described as an integer ≥ 2, it is equivalent to disclosing that the parameter can be, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0041] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0042] In the description of the embodiments of this application, the term "at least one" refers to one or more (including two).
[0043] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0044] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.
[0045] The present application will now be described with reference to specific embodiments. It should be noted that these embodiments are merely descriptive and do not limit the present application in any way.
[0046] The raw materials used in the following examples and comparative examples are of analytical or chemically pure purity. The source information of the raw materials is as follows:
[0047] Polyolefin elastomer 9147: self-supplied by Wanhua Chemical Group Co., Ltd.'s plant area;
[0048] Polyolefin elastomer 9057: self-supplied by Wanhua Chemical Group Co., Ltd.'s plant area;
[0049] Vinyltrimethoxysilane: >95%, Anhui Sibao Organosilicon New Materials Co., Ltd.;
[0050] Vinyltriethoxysilane: >95%, Anhui Sibao Organosilicon New Materials Co., Ltd.;
[0051] 3-(Methacryloxy)propyltrimethoxysilane (KH570): >95%, Anhui Sibao Organosilicon New Materials Co., Ltd.;
[0052] 2-Ethylhexyl tert-butyl percarbonate (TBEC): >95%, Lanzhou Additives Factory Co., Ltd.;
[0053] (2-Ethylhexyl) tert-amyl peroxide carbonate: >95%, Lanzhou Additives Factory Co., Ltd.;
[0054] 2-Ethylhexyl tert-butyl peroxide: >95%, Lanzhou Additives Factory Co., Ltd.;
[0055] Bis(2,2,6,6-tetramethylpiperidinyl) sebacate: >96%, Handan Furong Chemical Additives Co., Ltd.;
[0056] β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate n-octadecyl alcohol ester: 99.0%, Tianjin Lianlong New Material Co., Ltd.;
[0057] Pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid]: 98.0%, Tianjin Lianlong New Material Co., Ltd.;
[0058] Dioctyltin: 95%, Beijing Bailingwei Technology Co., Ltd.;
[0059] Triphenyltin: 99%, Shanghai Maclean Biochemical Technology Co., Ltd.;
[0060] Dibutyltin dilaurate: 95%, Shanghai Aladdin Biochemical Technology Co., Ltd.
[0061] Triallyl isocyanurate (TAIC): 98%, Beijing Bailingwei Technology Co., Ltd.;
[0062] Bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate (UV-770): 98%, Tianjin Lianlong New Material Co., Ltd.;
[0063] Antioxidant 1076: 99%, Tianjin Lianlong New Materials Co., Ltd.
[0064] Density test: Tested using a densitometer, according to ISO 1183 standard. Brand: Mettler Toledo, Model: EasyD40.
[0065] Grafting rate test: Relative grafting rate was tested using a Fourier transform infrared spectroscopy analyzer, referring to the testing standard GB / T 6040-2002, and calculated through characteristic peak area conversion. Brand: Thermo Fisher Scientific, Model iS10.
[0066] Additive absorption rate: The polyolefin elastomer particles prepared in each example and comparative example were poured into a transparent container with various additives (polyolefin elastomer particles: TBEC: TAIC: KH570: UV770: antioxidant 1076 = 100:1:0.6:0.2:0.1:0.1, mass ratio), mixed evenly, and 5g was taken out and placed in a 50℃ oven for 4h. Then, the surface of all particles was wiped with oil-absorbing paper, and m1 was weighed again. (m1 / 5)×100% is the additive absorption rate.
[0067] Peel strength: The test method refers to the China Photovoltaic Industry Association standard T / CPIA 0006—2017 "Copolyolefin film for photovoltaic module encapsulation".
[0068] PDI Front-Side Degradation: The polyolefin elastomers prepared in the examples and comparative examples (TBEC:TAIC:KH570:UV770:1076) were mixed in a mass ratio of 100:1:0.6:0.2:0.1:0.1, respectively, and used as the front and back encapsulation films for the same photovoltaic module. The photovoltaic module consists of tempered glass, upper encapsulation film, bifacial crystalline silicon solar cells, lower encapsulation film, and tempered glass. Crosslinking was performed at 150°C under vacuum and pressure for 18 minutes using a laminator. The power change of the module before and after HAST aging (85°C, 85%RH, 1500V, 192h) was tested.
[0069] Additive precipitation amount: According to the mass ratio, the polyolefin elastomers prepared in each example and the comparative example were mixed in the following proportions: TBEC:TAIC:KH570:UV770:1076 = 100:1:0.6:0.2:0.1:0.1. The mixture was placed at 50°C to allow the additives to be absorbed into the particles. The film was then prepared using a casting device at 90°C. 16g of the cast film was weighed and placed in 160g of anhydrous ethanol and soaked for 10min. 5g of anhydrous ethanol was taken for liquid chromatography analysis to quantitatively analyze the triallyl isocyanurate (TAIC) dissolved in the anhydrous ethanol.
[0070] Additive absorption time: The additive absorption time is determined by pouring the polyolefin elastomer particles provided in each example and comparative example with various additives (polyolefin elastomer particles: TBEC: TAIC: KH570: UV770: 1076 = 100:1: 0.6: 0.2: 0.1: 0.1, mass ratio) into a transparent container, mixing them evenly, and then placing them in a 50°C oven. Observe whether there is any oily additive residue on the surface of the transparent container and the dryness of the particle surface. If there is no residue and the particle surface is dry, it indicates that the additive has been completely absorbed, and the time is recorded.
[0071] Note: Heat and weather resistance are reflected by the PID test results, which are conducted under double 85 conditions (85℃, 85% humidity).
[0072] Example 1
[0073] This embodiment provides a method for preparing polyolefin elastomer particles, including the following steps:
[0074] Step 1: Weigh out polyolefin elastomer 9147, grafted monomer vinyltrimethoxysilane, initiator 2-ethylhexyl tert-butyl peroxide, UV stabilizer bis(2,2,6,6-tetramethylpiperidinyl) sebacate, and antioxidant β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate in the following mass ratios: 100 parts, 2 parts, 0.2 parts, 0.15 parts, and 0.1 parts. React the above raw materials in a twin-screw extruder (L / D ratio = 60, material residence time 2 minutes) at 190°C and extrude.
[0075] Step 2: The reactants from Step 1 are processed into reaction particles through an underwater pelletizing system (water temperature 5°C). The underwater pelletizing system is equipped with a self-circulating cooling water system. The catalyst dioctyltin is added to the water in advance at a rate of 0.5 mg / kg water.
[0076] Step 3: The reaction particles from Step 2 are passed through a vibrating screen (power 20kW) with a coarse screen (roughness Ra = 2μm, length 2m) to rub the particle surface, and then dried at room temperature to obtain modified polyolefin elastomer particles. The properties are shown in Table 1.
[0077] Example 2
[0078] This embodiment provides a method for preparing polyolefin elastomer particles, including the following steps:
[0079] Step 1: Weigh out polyolefin elastomer 9147, grafted monomer vinyltriethoxysilane, initiator 2-ethylhexyl tert-butyl peroxide, UV stabilizer bis(2,2,6,6-tetramethylpiperidinyl) sebacate, and antioxidant β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate in a mass ratio of 100 parts, 5 parts, 0.3 parts, 0.2 parts, and 0.2 parts, respectively. React the above raw materials at 190°C in a twin-screw extruder (L / D ratio = 58, material residence time (i.e., reaction time) 3 minutes, and then extrude.
[0080] Step 2: The reactants from Step 1 are processed into reaction particles through an underwater pelletizing system (water temperature 6°C). The underwater pelletizing system is equipped with a self-circulating cooling water system. The catalyst, dibutyltin dilaurate, is added to the water in advance at a rate of 1 mg / kg water.
[0081] Step 3: The reaction particles from Step 2 are rubbed on the particle surface by a vibrating screen (power 15kW) with a coarse screen (roughness Ra = 1.8μm, length 3m), and then air-dried at room temperature to obtain modified polyolefin elastomer particles. The properties are shown in Table 1.
[0082] Example 3
[0083] This embodiment provides a method for preparing polyolefin elastomer particles, including the following steps:
[0084] Step 1: Weigh out polyolefin elastomer 9147, grafted monomer 3-(methacryloyloxy)propyltrimethoxysilane, initiator tert-amyl peroxide (2-ethylhexyl) carbonate, UV stabilizer bis(2,2,6,6-tetramethylpiperidinyl) sebacate, and antioxidant β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate n-octadecyl alcohol ester in a mass ratio of 100 parts, 8 parts, 0.3 parts, 0.25 parts, and 0.1 parts. React the above raw materials in a twin-screw extruder (L / D ratio = 61, material residence time 4 minutes) at 190°C and extrude.
[0085] Step 2: The reactants from Step 1 are processed into reaction particles through an underwater pelletizing system (water temperature 7°C). The underwater pelletizing system is equipped with a self-circulating cooling water system. Triphenyltin catalyst is added to the water in advance at a concentration of 2 mg / kg water.
[0086] Step 3: The reaction particles from Step 2 are passed through a vibrating screen (30kW power) with a coarse screen (roughness Ra = 2.2μm, length 1m) to rub the particle surface, and then dried at room temperature to obtain modified polyolefin elastomer particles. The properties are shown in Table 1.
[0087] Example 4
[0088] This embodiment provides a method for preparing polyolefin elastomer particles, including the following steps:
[0089] Step 1: Weigh out polyolefin elastomer 9057, grafted monomer vinyltriethoxysilane, initiator tert-amyl peroxide (2-ethylhexyl) carbonate, UV stabilizer bis(2,2,6,6-tetramethylpiperidinyl) sebacate, and antioxidant pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] in the following mass ratios: 100 parts, 8 parts, 0.3 parts, 0.25 parts, and 0.1 parts. React the above raw materials at 190°C in a twin-screw extruder (L / D ratio = 61, material residence time 4 minutes) and extrude.
[0090] Step 2: The reactants from Step 1 are processed into reaction particles through an underwater pelletizing system (water temperature 7°C). The underwater pelletizing system is equipped with a self-circulating cooling water system. The catalyst, dibutyltin dilaurate, is added to the water in advance at a rate of 2 mg / kg water.
[0091] Step 3: The reaction particles from Step 2 are passed through a vibrating screen (power 20kW) with a coarse screen (roughness Ra = 2.3μm, length 1.5m) to rub the particle surface, and then dried at room temperature to obtain modified polyolefin elastomer particles. The properties are shown in Table 1.
[0092] Example 5
[0093] This embodiment provides a method for preparing polyolefin elastomer particles. The difference from Embodiment 2 is that in step 1, the aspect ratio L / D = 68, the material residence time is 7 minutes, and the reaction temperature is 180°C.
[0094] Comparative Example 1
[0095] This comparative example provides a method for preparing polyolefin elastomer particles, including the following steps:
[0096] Step 1: Weigh out polyolefin elastomer 9147, grafted monomer vinyltriethoxysilane, initiator 2-ethylhexyl tert-butyl peroxide, UV stabilizer bis(2,2,6,6-tetramethylpiperidinyl) sebacate, and antioxidant β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate in a mass ratio of 100 parts, 5 parts, 0.3 parts, 0.2 parts, and 0.2 parts, respectively. React the above raw materials in a twin-screw extruder (L / D ratio = 58, material residence time 3 minutes) at 190°C, extrude, and then pelletize underwater (without catalyst in the water).
[0097] Step 2: The reaction particles from Step 2 are passed through a vibrating screen (15kW) with a coarse screen (roughness Ra = 1.8μm, length 3m) to rub the particle surface, and then dried at room temperature to obtain modified polyolefin elastomer particles. The properties are shown in Table 1.
[0098] Comparative Example 2
[0099] This comparative example provides a method for preparing polyolefin elastomer particles, including the following steps:
[0100] Step 1: Weigh out polyolefin elastomer 9147, grafted monomer vinyltriethoxysilane, initiator 2-ethylhexyl tert-butyl peroxide, UV stabilizer bis(2,2,6,6-tetramethylpiperidinyl) sebacate, and antioxidant β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate in a mass ratio of 100 parts, 5 parts, 0.3 parts, 0.2 parts, and 0.2 parts, respectively. React the above raw materials in a twin-screw extruder (L / D ratio = 58, material residence time 3 minutes) at 190°C and extrude.
[0101] Step 2: The reactants from Step 1 are processed into reaction particles through an underwater pelletizing system (water temperature 6°C). The underwater pelletizing system is equipped with a self-circulating cooling water system. The catalyst, dibutyltin dilaurate, is added to the water in advance at a rate of 1 mg / kg water.
[0102] Step 3: After drying the reaction particles from Step 2, modified polyolefin elastomer particles are obtained, and their properties are shown in Table 1.
[0103] Comparative Example 3
[0104] This comparative example provides a method for preparing polyolefin elastomer particles, in which no initiator is added in step 1 compared to Example 4.
[0105] Comparative Example 4
[0106] This comparative example provides a method for preparing polyolefin elastomer particles, in which no grafted monomer is added in step 1 compared to Example 4.
[0107] Test Results
[0108] The performance test results of the polyolefin elastomer particles provided in each embodiment and comparative example are shown in the table below:
[0109] Table 1
[0110]
[0111] As can be seen from the data in Table 1 of the examples and comparative examples, the polyolefin elastomer particles prepared in this application are significantly better than the comparative examples in terms of additive absorption rate, peel strength of the film, and resistance to PID degradation. The polyolefin elastomer particles provided in the examples of this application can effectively reduce the problem of additive migration in the film and improve the resistance to PID. Figure 1 and Figure 2 The images show SEM images of the polyolefin elastomer particles provided in Example 1 and Comparative Example 2 of this application. As can be seen from the images, the surface roughness of the polyolefin elastomer particles prepared in the examples of this application is significantly improved. Combined with the surface-adsorbed catalyst, the absorption rate of the additives can be significantly improved, thereby improving the performance of the film.
[0112] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A method for preparing polyolefin elastomer particles, characterized in that, Includes the following steps: S1, reacting a polyolefin elastomer, graft monomer, initiator, UV stabilizer, and antioxidant to obtain a mixture; the graft monomer includes at least one selected from 3-(methacryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, and vinyltri(2-methoxyethoxy)silane; the amount of graft monomer is 0.5-10 parts per 100 parts by weight of polyolefin elastomer; S2, the mixture is extruded and pelletized in water containing catalyst to obtain reaction particles; the ratio of catalyst to water in the catalyst-containing water is 0.05-3 mg / kg, and the catalyst includes at least one of tin-containing catalyst or bismuth-containing catalyst; S3, the surface of the reactant particles is roughened to obtain polyolefin elastomer particles.
2. The method for preparing polyolefin elastomer particles according to claim 1, characterized in that, In S2, the temperature of the water containing the catalyst is 5-10℃; And / or, the catalyst comprises at least one of dioctyltin, triphenyltin, dibutyltin dilaurate, bis(monoctyl maleate) di-n-butyltin, di-n-octyltin maleate, and bismuth neodecanoate.
3. The method for preparing polyolefin elastomer particles according to claim 1, characterized in that, In S3, a vibrating screen is used to roughen the surface of the reaction particles.
4. The method for preparing polyolefin elastomer particles according to claim 3, characterized in that, The vibrating screen has a roughness Ra≥1.5μm; a length of 1-3m; and a power of 10-30kW.
5. The method for preparing polyolefin elastomer particles according to claim 4, characterized in that, The roughness of the vibrating screen is 1.5-10 μm.
6. The method for preparing polyolefin elastomer particles according to claim 1, characterized in that, In S1, the reaction temperature is 180-220℃ and the reaction time is 1-8 min.
7. The method for preparing polyolefin elastomer particles according to any one of claims 1-6, characterized in that, The mass fractions of each component are as follows: 100 parts polyolefin elastomer, 0.5-10 parts grafted monomer, 0.05-0.5 parts initiator, 0.05-0.3 parts UV stabilizer, and 0.1-0.6 parts antioxidant. And / or, in S1, the reaction time is 1-5 min.
8. The method for preparing polyolefin elastomer particles according to claim 7, characterized in that, The polyolefin elastomer includes at least one of ethylene-propylene copolymer, ethylene-butene copolymer, ethylene-hexene copolymer, ethylene-octene copolymer, styrene-butadiene-styrene block copolymer, and ethylene-propylene-α-olefin copolymer; And / or, the initiator includes at least one of organic peroxide initiators, inorganic peroxide initiators, and azo initiators; And / or, the UV stabilizer comprises at least one of tris(1,2,2,6,6-pentamethyl-4-piperidinyl) phosphite, hexadecyl 3,5-di-tert-butyl-4-hydroxybenzoate, bis(2,2,6,6-tetramethylpiperidinyl) sebacate, and bis(1-octoxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate; And / or, the antioxidant comprises one of 2,6-di-tert-butyl-p-cresol, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexamethylenediamine, 4,4'-thiobis(3-methyl-6-tert-butylphenol), and tris(2,4-di-tert-butylphenyl)phosphite.
9. The method for preparing polyolefin elastomer particles according to claim 7, characterized in that, The initiator includes at least one of 2,5-dimethyl-2,5-bis(tert-butylperoxide)hexane, dicumyl peroxide, di-tert-butylperoxide, tert-butyl peroxide-2-ethylhexyl carbonate, tert-butyl peroxide-2-ethylhexyl carbonate, and tert-amyl peroxide-2-ethylhexyl carbonate.
10. The method for preparing polyolefin elastomer particles according to any one of claims 1-6 or 8-9, characterized in that, In S2, a twin-screw extruder is used for extrusion, and the length-to-diameter ratio (L / D) of the twin-screw extruder is ≥55.
11. The method for preparing polyolefin elastomer particles according to claim 10, characterized in that, In S2, the length-to-diameter ratio of the twin-screw extruder is 56≤L / D≤65.
12. A polyolefin elastomer particle, characterized in that, It is prepared by the preparation method according to any one of claims 1-11.
13. The use of the polyolefin elastomer particles of claim 12 in an adhesive film.
Citation Information
Patent Citations
Modified polyurethane with biocompatibility, high strength, high temperature resistance and high resilience as well as preparation and application of modified polyurethane
CN112898521A
Precipitation-preventing and crosslinking-assisting polyolefin grafting material as well as preparation method and application thereof
CN118894968A